Fréchet-valued holomorphic functions on compact sets in (DFN)-spaces - Pham Hien Bang (Український математичний журнал, 2008)
The aim of this paper is to give the equivalence between the weak holomorphicity and the holomorphicity
of Frechet-valued functions on compact polydiscs in (DFN)-spaces. Moreover, the relations between
separately holomorphic functions and holomorphic functions on compact polydiscs in (DFN)-spaces are
also given. Мета цієї статті — встановити еквiвалентнiсть між слабкою голоморфністю та голоморфністю Фреше-значних функцій на компактних полідисках у (DFN)-просторах. Також наведено співвідношення між нарізно голоморфними функціями та голоморфними функціями на компактних полідисках у (DFN)-просторах.